2014
DOI: 10.1097/mph.0000000000000204
|View full text |Cite
|
Sign up to set email alerts
|

Massive Splenic Infarction and Portal Vein Thrombosis in Children With Chronic Myeloid Leukemia

Abstract: Massive splenic infarction and portal vein thrombosis (PVT) due to chronic myeloid leukemia (CML) is extremely rare. We describe 2 children who were presented with massive splenic infarction and PVT in the course of CML. Massive splenic infarction and PVT treated with splenectomy in one and with medical treatment in another in whom PVT resolved by cytoreductive treatment, led to downsizing of spleen or splenectomy. Splenic infarct and PVT should be considered in CML patients with long-lasting severe abdominal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…If we evaluated the literature on children with hematological disorders, we could state that splenectomy is indicated in cases of persistent abdominal pain, splenic abscesses, splenic infarct, hemorrhage, pseudocyst formation and rupture of the spleen (37,38,40). Patrono et al reported successful and effective LS following splenic artery embolization in an adult patient with chronic pancreatitis-related splenic vein thrombosis causing leftsided portal hypertension (41).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If we evaluated the literature on children with hematological disorders, we could state that splenectomy is indicated in cases of persistent abdominal pain, splenic abscesses, splenic infarct, hemorrhage, pseudocyst formation and rupture of the spleen (37,38,40). Patrono et al reported successful and effective LS following splenic artery embolization in an adult patient with chronic pancreatitis-related splenic vein thrombosis causing leftsided portal hypertension (41).…”
Section: Resultsmentioning
confidence: 99%
“…The postoperative complications rate varied from 0% to 35.7% (6,9,10,14,18,(45)(46)(47)(48)(49). Postoperative complications include bleeding (12,17), PVT (12,19,21), subphrenic abscess formation (13,21), intestinal ischemia (40), pancreatic leakage (9), wound infections and respiratory complications (13). The reoperation rates varied from 0% to 6.7% (6-14, 17, 18, 20, 25, 27, 35, 36, 53).…”
Section: Resultsmentioning
confidence: 99%
“…As far as we know, there has been no previous report of fatal embolisms in a patient with EMPD. Generally, portal and splenic vein embolisms can occur in patients with malignancies around the portal or splenic vein [5][6][7]. However, our patient had no metastatic lesions around the abdominal cavity.…”
mentioning
confidence: 56%
“…При этом относительно часто ИС имеет характер массивного поражения (более 50 % пло щади по оценке КТизображения), что почти в 75 % случаев требует выполне ния спленэктомии [2]. Известно разви тие ИС на фоне миелолейкоза [1]. Уни кальными являются наблюдения ИС у ребенка на фоне перекрута нормально расположенной селезенки, когда точная диагностика стала возможной только благодаря применению методов луче вой визуализации [11].…”
Section: особенности инфаркта селезенки у детей и подростковunclassified